132 Treating (or Monitoring?) Low-Risk Ductal Carcinoma in Situ (DCIS): Focus Groups about Women's Views. (8th June 2022) - Hersch, Jolyn; Nickel, Brooke; Dixon, Ann; Jansen, Jesse; Saunders, Christobel; Houssami, Nehmat; Barratt, Alexandra; Spillane, Andrew; Stuart, Kirsty; Rutherford, Claudia; Robertson, Geraldine; Wylie, Liz; et al.
Abstract : Objectives: Organised breast screening has greatly increased DCIS incidence. Recognition that some DCIS lesions might remain indolent for many years has led to concern about overtreatment, and international clinical trials are currently assessing the safety of active monitoring for low-risk DCIS. Women may not be aware of what DCIS is and the dilemmas around its optimal management. We aimed to explore women's understanding and views about DCIS and current and potential future management options. Method: A community-based sample, recruited by telephone, of 56 women aged 50–74 with no personal history of breast cancer/DCIS participated in six age-stratified focus groups around Sydney, Australia. Sessions incorporated a purpose-designed presentation explaining the nature of DCIS, current standard management, uncertainty around progression, and ongoing clinical trials of monitoring for low-risk DCIS. Throughout the sessions, participants shared their thoughts, feelings and questions in response to the information presented. Discussions were audio-recorded, transcribed and analysed thematically. Results: Very few participants had heard of DCIS. Many women showed interest in being monitored if diagnosed with low-risk DCIS; others expressed stronger preference for immediate treatment. Although women mostly supported clinical trials of monitoring (and just over half would join if invited), they also had important concerns and misconceptions about such trials. Some participants struggled to understand the need for randomisation. Many would be reluctant to leave their management to chance, including some who felt strongly against surgery if monitoring were considered viable. Conclusions: Public awareness of DCIS is very limited. Most focus group participants gained a reasonable understanding of the issues during the session, and we found substantial interest in monitoring for low-risk DCIS. If clinical trials are to generate much-needed high-quality evidence about new management approaches, effective communication is essential to facilitate informed decisions about screening, treatment and trial participation, and to implement future changes in practice.